PENGARUH KONFORMITAS TEMAN SEBAYA, MOTIVASI DAN MINAT KARIR TERHADAP PEMILIHAN PROGRAM STUDI AKUNTANSI DI PERGURUAN TINGGI - Istiqomah Istiqomah; Lilik Sri Hariani; Affan Afian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
Peer conformity, motivation, and career interests influence the selection of Accounting study programs in Higher Education. Peer conformity is common in the social environment of students, highly motivated, and career interests make students interested in choosing Accounting study programs. The purpose of this study was to determine the effect of peer conformity, motivation, and career interests on the selection of accounting study programs in tertiary institutions. The research method uses quantitative methods using multiple linear regression. The population in this study were all students of the Unikama Accounting study program totaling 665 students with a research sample of 100 students. The sampling technique uses stratified random sampling method. analyzing data with the help of SPSS application version 22.00 for windows. Based on the results of calculations, it is known that there is an influence of peer conformity, motivation, and career interests simultaneously on the selection of accounting study programs in Higher Education both partially and simultaneously. Choosing a study program should be chosen in accordance with the foreseeable consideration in accordance with interests, talents, and abilities.